2011
DOI: 10.1128/jvi.02398-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Poliovirus Protein 3A Interactions with Viral and Cellular Proteins in Infected Cells

Abstract: Poliovirus proteins 3A and 3AB are small, membrane-binding proteins that play multiple roles in viral RNA replication complex formation and function. In the infected cell, these proteins associate with other viral and cellular proteins as part of a supramolecular complex whose structure and composition are unknown. We isolated viable viruses with three different epitope tags (FLAG, hemagglutinin [HA], and c-myc) inserted into the N-terminal region of protein 3A. These viruses exhibited growth properties and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 41 publications
8
58
0
Order By: Relevance
“…FLAG and GST were detected by Western blotting with antibodies directed against FLAG and GST, respectively. region of 3A has been shown to tolerate small insertions, which do not prevent the generation of viruses (43)(44)(45). We first confirmed that FLAG epitope insertion had no effect on viral growth compared to the parental PVS2 and PVS2-3A(CV-A17) (Fig.…”
Section: Resultssupporting
confidence: 55%
“…FLAG and GST were detected by Western blotting with antibodies directed against FLAG and GST, respectively. region of 3A has been shown to tolerate small insertions, which do not prevent the generation of viruses (43)(44)(45). We first confirmed that FLAG epitope insertion had no effect on viral growth compared to the parental PVS2 and PVS2-3A(CV-A17) (Fig.…”
Section: Resultssupporting
confidence: 55%
“…VCP interacted with the C-terminal region of 3AB (aa 42 to 87 of 3A) in contrast to GBF1 and PI4KB, which interacted with 3AB via the N-terminal region of 3A (aa 1 to 41 of 3A) (Fig. 4B) (33,43,86,91). This suggested that the interaction of VCP with 3AB occurs independently of that of GBF1/PI4KB.…”
Section: Discussionmentioning
confidence: 97%
“…While attempts were made to produce infectious virus bearing green fluorescent protein (GFP), luciferase, or other reporters at a number of the validated sites, none resulted in the production of infection virus (data not shown). Therefore, the FLAG tag (DYKDDDDK) was next selected for insertion due to its small size and success with other small positive-strand RNA viruses (71). The FLAG tag was inserted into a site in both NS4 (nt 2600) and VP2 (nt 6686), both of which were stable validated sites in proteins of largely unknown function (Fig.…”
Section: Figmentioning
confidence: 99%
“…These have included sequences encoding reporter proteins or small peptide tags to facilitate further characterization of the viral proteins and their interaction partners, as well as to enable imaging of viral replication (1,5,45,70,71). This strategy has been particularly successful for labeling small positive-strand RNA viruses (69,70), for which traditional approaches, such as making insertions in the viral UTRs (51) or targeted viral protein-reporter fusions (11), are challenging.…”
mentioning
confidence: 99%